2002
DOI: 10.1074/jbc.m111726200
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Reconstitution, and Steady-state Kinetics of the Trans-membrane 17β-Hydroxysteroid Dehydrogenase 2

Abstract: Human membrane 17␤-hydroxysteroid dehydrogenase 2 is an enzyme essential in the conversion of the highly active 17␤-hydroxysteroids into their inactive keto forms in a variety of tissues. 17␤-hydroxysteroid dehydrogenase 2 with 6 consecutive histidines at its N terminus was expressed in Sf9 insect cells. This recombinant protein retained its biological activity and facilitated the enzyme purification and provided the most suitable form in our studies. Dodecyl-␤-D-maltoside was found to be the best detergent fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…[E2]/[E1] ratio was unchanged by the addition of 0.5 mM NAD to T47D and MCF-7-17β-HSD1 cells (with higher expression of 17β-HSD1 and lower expression of 17β-HSD2), whereas it was decreased by the addition of 0.5 mM NADP. The Kcat/Km value for 17β-HSD2 using NAD is 400 times greater than that using NADP, so NAD is the preferred cofactor for its major role in E2 oxidation [15]. In addition, the specificity of 17β-HSD2 to NAD is around 3 times higher than that of 17β-HSD1 [14][16].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[E2]/[E1] ratio was unchanged by the addition of 0.5 mM NAD to T47D and MCF-7-17β-HSD1 cells (with higher expression of 17β-HSD1 and lower expression of 17β-HSD2), whereas it was decreased by the addition of 0.5 mM NADP. The Kcat/Km value for 17β-HSD2 using NAD is 400 times greater than that using NADP, so NAD is the preferred cofactor for its major role in E2 oxidation [15]. In addition, the specificity of 17β-HSD2 to NAD is around 3 times higher than that of 17β-HSD1 [14][16].…”
Section: Discussionmentioning
confidence: 98%
“…The highly active 17β-HSD1 plays an important role in E2 synthesis using NADPH as cofactor, with a Km value of 0.03±0.01 µM [14]. 17β-HSD2 plays an important role in E1 production using NAD as cofactor, with a Km value of 0.35±0.09 µM [15]. In some estrogen-dependent breast cancer cells, 17β-HSD1 is more abundantly expressed than 17β-HSD2 [16][18].…”
Section: Introductionmentioning
confidence: 99%
“…AKR1C3 catalyzes reduction of estrone ( K d = 0.3 nM for ERα and ERβ) to yield the more potent estrogen 17β-estradiol, ( K d = 0.1 nM for ERα and ERβ) and thus controls activation of ERα and ERβ [37]. The reverse reaction is catalyzed by HSD17B2 also designated as SDR9C2 [49, 50]. Thus these reactions represent molecular switches that can finely tune and control ligand occupancy of the ER.…”
Section: Akr1 Enzymes Control Concentrations Of Receptor Ligandsmentioning
confidence: 99%
“…However, it proved impossible to extract any VGLUT1 from the insect cell membranes using Cholate or CHAPS (data not shown), and no protein was found bound to the Talon beads using these conditions (data not shown). Previous accounts on Baculovirus-expression of membrane proteins have indicated that Cholate (or CHAPS) extract poorly proteins from insect cell membranes (14). Guided by these observations (14), by substituting Cholate/CHAPS with 1% n-decyl-β-d-maltopyranoside, and using otherwise identical conditions to those used for the PC12 based purification, it was found possible to extract VGLUT1 from the insect cell membranes (Fig.…”
Section: Resultsmentioning
confidence: 99%